(untitled) (Medico Legal Update, 2020)
Introduction. Pregnant women have a risk for tobacco smoke both actively and passively. Pregnant women are usually exposed to enviromental tobacco smoke (ETS) in various places with different duration of time. Cigarette smoke has a severe effect not only on pregnant women but also on the fetus.Methods Various references were collected from online database including reports, journals, mostly in the last 10 years. The journals were mostly from the scholarly journals. Results. Tobacco smoke can effect the immunity, hormonal and metabolic system of the pregnant woman, therefore disturbing the growth of the fetus. Tobacco smoke also known to increase the risk of premature birth and reduce gestational age. Tobacco smoke cause several problems in newborn such as respiration distress, low birth weight (LBW), neural disorder, sudden infant death syndrome (SIDS) and congenital anomaly. Conclusion. The effect of tobacco smoke, actively of passively, have worse outcome for the pregnant women and their babies.